'Marriage', 'Massage', Metaphor and Gender in US–Iranian Relations During the 1960s. Issue 1 (2nd January 2020) - Offiler, Ben
Abstract: Although they were allies, during the 1960s relations between the United States and Iran were fraught with tensions. For American policymakers, Iran was an important Cold War client and oil-supplier in a turbulent region. It was vital, therefore, to maintain a good relationship with the Shah of Iran. Indeed, United States policy was based in large part on American assessments of the Shah as an individual. This article seeks to assess how the language and metaphors used by American policymakers to describe and understand the Shah reflected and informed United States policy. Officials within the Kennedy and Johnson administrations viewed the Shah through a highly gendered lens that magnified perceptions of him as a weak, highly sensitive and irrational leader – characteristics deemed to be overly feminine. This article therefore contends that US policy towards Iran was influenced by gender stereotypes as policymakers lamented their reliance on the Shah, who they deemed to be insufficiently 'masculine'.